2020
DOI: 10.1116/6.0000718
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of improved power conversion efficiency in lead-free CsGeI3 based perovskite solar cell heterostructure via scaps simulation

Abstract: Simulation has been performed on fully lead-free inorganic cesium germanium tri-iodide (CsGeI3) perovskite solar cell heterostructure and achieved a champion power conversion efficiency (PCE) of ∼18.30% with significantly improved device parameters. The influence of thickness of an electron transport layer, a hole transport layer, an absorber, defect density, doping concentration, electron affinity, temperature, and series resistance issued for the optimization of the lead-free device is studied. It is confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 71 publications
0
64
0
Order By: Relevance
“…23 In addition, it has been predicted that the total power-conversion efficiency (PCE) of the CsGeI 3 solar cell devices can reach 18.3%, which is influenced by the thickness of electron affinity, temperature, electron transport layer, hole transport layer, defect density, doping concentration, absorber, and series resistance on the optimization of the lead-free device. 24 These good experimental and theoretical prediction results showed that Ge-based perovskites are promising materials for photovoltaic and optoelectronic devices. The bandgap size, orbital information, and electronic contribution can be obtained by calculating electronic properties.…”
Section: Introductionmentioning
confidence: 94%
“…23 In addition, it has been predicted that the total power-conversion efficiency (PCE) of the CsGeI 3 solar cell devices can reach 18.3%, which is influenced by the thickness of electron affinity, temperature, electron transport layer, hole transport layer, defect density, doping concentration, absorber, and series resistance on the optimization of the lead-free device. 24 These good experimental and theoretical prediction results showed that Ge-based perovskites are promising materials for photovoltaic and optoelectronic devices. The bandgap size, orbital information, and electronic contribution can be obtained by calculating electronic properties.…”
Section: Introductionmentioning
confidence: 94%
“…Parameter TCO [11,44,45] PCBM [46,47] CsPbI 3 [48][49][50] CsSnI 3 [51,52] CsGeI 3 [15] MAPbI 3 [53,54] Cu 2 O [32] Thickness [nm] 500 a) 30 a) 1400 a) 1200 a) 1500 a) 1800 a) 50 a)…”
Section: Influence Of Dopant Concentration Of the Absorber Layermentioning
confidence: 99%
“…[ 14 ] Recent simulation studies on CsGeI 3 ‐based PSCs with TiO 2 and SpiroMeOTAD as transport layers shows that a PCE of 18.30% can be achieved through proper optimization of the device input parameters. [ 15 ] However, the experimental fabrication of the solar cell with CsGeI 3 as the absorber layer and TiO 2 and SpiroMeOTAD as the transport layers exhibited a PCE of 0.11% only. [ 16 ] The large disparity in PCE values observed experimentally and theoretically for CsPbI 3 ‐, CsSnI 3 ‐, and CsGeI 3 ‐based PSCs indicates that extended research is needed to determine the best combination of materials to employ as various layers in the PSC.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 shows the J-V characteristics of different FTO/TiO 2 /lead-free perovskite/CZTS/ Au structures; the lead-free perovskites used in this graph were: MASnI 3 , FASnI 3 , Cs 2 TiBr 6 , (FA) 2 BiCuI 6 and CsGeI 3 [13,[24][25][26][27]. 𝐷 𝑛(𝑝) diffusion coefficient of electrons and holes.…”
Section: Figure 2 J−v Characteristics Of Lead-free N-i-p Pscsmentioning
confidence: 99%